Turner's Syndrome - genetic, diagnostic methods and clinical treatment - Aleksandra Łokczewska-Bojar; Rami Ben Rhaiem; Przemysław Kępka; Daria Kuziemkowska; Jan Kuźma; Anna Łącka-Majcher; Grzegorz Tarsa; Magdalena Skotalczyk; Zuzanna Sawińska; Katarzyna Sudelska (Kazimierz Wielki University, 2023)
Introduction : Turner syndrome (TS) is one of the most common genetic disorders affecting approximatley 1 in 2,000-25000 live-born girls. TS is the result of complete oraz partial monosomy of the C chromosome. About half have monosomy X (45,X) and 5-10% have duplication (isochromosome) of the long arm of one X (46,X,i(Xq)). Most of the rest have mosaicism.(1)  The aim of the study: The purpose of this review paper is to present the observations regarding this disease, including epidemiology, diagnosis and detailed examination of the individual needs of the patient affected by the disease.  Matrials and methods: This review was based on available data collected in the PubMed database and Google Scholar web serach engine, using key words: Turner's syndrome, diagnosis of Turner Syndrome, sex chromosome aneuploidies  Summary: The article draws attention to the complexity of Turner syndrome, the variety of symptoms and the progress in the diagnosis and therapy of this disease. Early diagnosis, specialist care and modern therapeutic methods have a positive impact on the quality of life of TS patients. Future studies of molecular mechanisms and therapeutic efficacy may improve the care of patients affected by this rare disease.